PENGEMBANGAN EKONOMI HIJAU MELALUI PEMBERDAYAAN MASYARAKAT MELALUI SEKTOR PERKEBUNAN DI DESA SELELOS - Insani, Nafaza Nur; Jannah, Alya Raudhatul; fahir, Muhammad; Wulansari, Arum; Rahmah, Fadila Ulya; Nazah, Gebrilla Niftita; Wiradharma, I Gde Putu Vigneswara Angga; Ardiansyah, Lalu Muhammad Ari; Chair, Salma; Salsabila, Violeta Karin (Jurnal Wicara, 2024)
Real Work Lectures (KKN) are a form of student service to the community as part of the third "Tridharma of Higher Education", namely community service. In 2024, the University of Mataram KKN will carry a green economy theme which aims to empower village communities through various activities that focus on improving welfare and environmental sustainability. One of the locations for implementing KKN is Selelos Village, Gangga District, North Lombok Regency, a village with a topographical character of plains and hills and various social problems, such as a lack of attention to plantation crops and the environment. This KKN activity aims to overcome these problems by implementing main programs, such as training in making compost from plantation waste, socialization of environmental law, as well as training in integrated pest and plant disease control. Through this program, it is hoped that community awareness and ability can be created to protect the environment and increase plantation productivity in Selelos Village.